Interaction between Islamic Financial Development and Economic Growth: Empirical Evidence from Indonesia - Ambariyanto Ambariyanto; Muslich Anshori; Imron Mawardi; R Moh Qudsi Fauzi (MediaTrend, 2023)
Financial development and economic growth have been thoroughly analyzed in the literature extensively. The discussion revolved on whether the financial sector leads the real sector in the process of economic development or whether it is the other way around. There is now no consensus on the causal relationship between financial development and economic growth. So, it is necessary to determine the relationship between financial development and economic growth in order to make accurate economic growth estimations. This paper examines an interaction model between Islamic financial development and economic growth that assumes the consumption of real resources by the financial sector. This research used Hadri Lagrange-Multiplier to investigate association’s path between variables. As a result, the interaction between Islamic financial development and economic growth may be unidirectional. However, the Islamic financial system is unsustainable, the Islamic financial market's contribution remains modest, and this could not eventually contribute to economic growth significantly. In addition, the results of this study reveal that the development of Islamic financial institutions in Indonesia has not yet had a significant effect on the welfare of Indonesian society. Due to rising demand for financial services, it was believed that economic growth drives finance in developing nations. Moreover, Economic growth fosters competition among financial intermediaries, resulting in more efficient financial transactions and, consequently, increased growth.